Health policy privatization and participation of the population controlled - Leon Pretel, Pricila (2013)
This research reports on the characteristics and application of health policy in Peru since the 90s, implementing economic measures contained in the Washington Agreement. Specifically on the aspect of privatization to the poorest stratum of the country (rural and urban). Describes the neoliberal politics based on individualism and how Peruvian are divested of a right which is recognized in many treaties, as is health. It presents and analyzes the experience of Local Committees of Shared Administration in Health at national level, recognizing the improvements in the services, but also showing how in the co-management of the services of this sector the State establishes norms and implements the community involvement without decision and without representation; finally the participation is defined as passive and controlled without demeriting that in some places there have been closer results to real participation of the population.